Novel agricultural non-point source pollution ecological interception ditch - MA XIAODONG; WANG WANBIN; JIA HAIFENG; LI SEN; GUAN TANGZHEN (2022)
The novel agricultural non-point source pollution ecological interception ditch comprises a sedimentation tank, a first drainage ditch and a second drainage ditch are arranged on the outer walls of the two sides of the sedimentation tank respectively, a movable frame is connected to the inner wall of the sedimentation tank in a sliding mode, and a fourth filter plate and a third filter plate are fixed to the outer wall of the top of the movable frame. A storage frame is fixed to the outer wall of one side of the movable frame and slidably connected to the inner wall of the sedimentation tank, a baffle is fixed to the inner wall of the sedimentation tank, an L-shaped supporting rod is fixed to the outer wall of the top of the sedimentation tank, an electric hoist is fixed to the outer wall of one side of the L-shaped supporting rod, and the outer wall of the top of the baffle is lower than the outer walls of the tops of the first drainage ditch and the second drainage ditch. A control panel is fixed to the out